Comprehensive nonlinear aeroelastic modeling and comparative analysis of continuous wing-based systems - Yossri, W.; Bouma, A.; Ben Ayed, S.; Vasconcellos, R. [UNESP]; Abdelkefi, A.; AIAA (Amer Inst Aeronautics & Astronautics, 2021)
Nowadays, wing-based systems represent imperative built-in constituents of many structures in a variety of fields. Consequently, robust modeling capable of accurately predicting such systems' responses is an intriguing key of interest for different studies towards potential competing optimized designs. In this work, a comprehensive aeroelastic study is conducted. The purpose of this effort is to compare the effects of using the quasi-steady versus the unsteady formulation for both linear and nonlinear regimes. The linear analysis focuses on the determination of the onset speed of flutter when both approximations are used. The nonlinear analysis, on the other hand, is performed to investigate the stall effect on the system's response. The nonlinear reduced-order model of the system's aeroelastic response is derived using the extended Hamilton's principle and Galerkin discretization. Results show that, for a highly coupled fluid-structure interaction problem, the quasi-steady formulation underpredicts the onset of flutter and that the stall coefficient hugely affects both the bending and torsion amplitudes in the post-flutter regime.